Venetoclax-Based Combinations in Acute Myeloid Leukemia: Current Evidence and Future Directions - Samra, Bachar; Konopleva, Marina; Isidori, Alessandro; Daver, Naval; DiNardo, Courtney (Frontiers in Oncology, 2020)
The past decade has witnessed major advances in our understanding of molecular biology, which led to breakthrough novel therapies, importantly including the B-cell lymphoma-2 (BCL-2) inhibitor venetoclax. Notably, venetoclax-based combinations have improved outcomes, including both remission rates and overall survival, of older patients with acute myeloid leukemia (AML) deemed “unfit” for intensive chemotherapy due to age or comorbidities. This has translated into a rapid and widespread use of venetoclax-based combinations in both academic and community-based settings. Other venetoclax-based combinations are being investigated in AML with the ultimate goal of improving cure rates across many subgroups; frontline and relapsed/refractory, in combination with intensive chemotherapy, in the post- transplant setting, or as maintenance strategy. In this article, we summarize the current available data on venetoclax-based combinations. We also highlight areas of unmet medical need, and we offer practical clinical pearls for management of patients receiving such therapy.